Potential impact of task-shifting on costs of antiretroviral therapy and physician supply in Uganda - Stergachis Andy; Kambugu Andrew; Lamorde Mohammed; Castelnuovo Barbara; Babigumira Joseph B; Easterbrook Philippa; Garrison Louis P (BMC, 2009)
Abstract Background Lower-income countries face severe health worker shortages. Recent evidence suggests that this problem can be mitigated by task-shifting--delegation of aspects of health care to less specialized health workers. We estimated the potential impact of task-shifting on costs of antiretroviral therapy (ART) and physician supply in Uganda. The study was performed at the Infectious Diseases Institute (IDI) clinic, a large urban HIV clinic. Methods We built an aggregate cost-minimization model from societal and Ministry of Health (MOH) perspectives. We compared physician-intensive follow-up (PF), the standard of care, with two methods of task-shifting: nurse-intensive follow-up (NF) and pharmacy-worker intensive follow-up (PWF). We estimated personnel and patient time use using a time-motion survey. We obtained unit costs from IDI and the literature. We estimated physician personnel impact by calculating full time equivalent (FTE) physicians saved. We made national projections for Uganda. Results Annual mean costs of follow-up per patient were $59.88 (societal) and $31.68 (medical) for PF, $44.58 (societal) and $24.58 (medical) for NF and $18.66 (societal) and $10.5 (medical) for PWF. Annual national societal ART follow-up expenditure was $5.92 million using PF, $4.41 million using NF and $1.85 million using PWF, potentially saving $1.51 million annually by using NF and $4.07 million annually by using PWF instead of PF. Annual national MOH expenditure was $3.14 million for PF, $2.43 million for NF and $1.04 for PWF, potentially saving $0.70 million by using NF and $2.10 million by using PWF instead of PF. Projected national physician personnel needs were 108 FTE doctors to implement PF and 18 FTE doctors to implement NF or PWF. Task-shifting from PF to NF or PWF would potentially save 90 FTE physicians, 4.1% of the national physician workforce or 0.3 FTE physicians per 100,000 population. Conclusion Task-shifting results in substantial cost and physician personnel savings in ART follow-up in Uganda and can contribute to mitigating the heath worker crisis.